Case report: Withdrawal of angiotensin-converting enzyme inhibitors in children with advanced chronic kidney disease and rapidly declining kidney function - Seeman, Tomáš; Dušek, Jiří (Frontiers in Pediatrics, 2023)
Background It is not known whether withdrawal of angiotensin-converting enzyme inhibitors (ACEIs) in children with advanced chronic kidney disease (CKD) is beneficial similar to adults. We report a case series of children with advanced CKD whose ACEIs were stopped. Methods In the last 5 years, we stopped ACEIs in seven consecutive children on ACEI therapy with rapidly declining CKD stage 4–5. The median age was 12.5 years (range 6.8–17.6); the median estimated glomerular filtration rate (eGFR) at stopping ACEIs was 12.5 ml/min/1.73 m2 (range 8.8–19.9). Results Six to twelve months after stopping ACEIs, the eGFR increased in five children (71%). The median absolute increase of eGFR was 5.0 ml/min/1.73 m2 (range −2.3 to +20.0) and relative increase of eGFR was 30% (range −34 to +99). The median follow-up after stopping ACEIs was 2.7 (range 0.5–5.0) years, either until the start of dialysis (n = 5) or until the last follow-up without dialysis (n = 2). Conclusions This case series showed that withdrawal of ACEIs in children with CKD stage 4–5 and rapidly declining kidney function may lead to an increase in eGFR.